Pengaruh Media Tanam Berbahan Dasar Cocopeat Pada Pembibitan Kakao (Theobroma cacao L.) - Vina Ayesta Ardilla; Wilna Sari; Kiki Amelia; Mentari Larashinda (UNIVERSITAS LABUHANBATU, 2026)
Cocoa (Theobroma cacao L.) is a plantation crop of high economic value that requires high-quality seedlings to support optimal field productivity. One of the main constraints in cocoa nurseries, particularly for the Trinitario variety in Jorong Kampung Juar, Nagari Tanjung, is the use of planting media derived from burned soil, which is generally low in nutrients and may contain potentially toxic compounds. Cocopeat, a by-product of coconut husk processing, has potential as an alternative growing medium due to its physical properties, including high water-holding capacity, improved aeration, and a pH suitable for cocoa growth. This study aimed to evaluate the effects of different cocopeat-based growing media compositions on the growth of cocoa seedlings and to assess their suitability as an alternative nursery medium. The study employed a Completely Randomized Design (CRD) with four treatments and five replications. The treatments consisted of soil and goat manure as the control, and three cocopeat application rates of 450 g, 550 g, and 650 g per polybag. Observed parameters included plant height, number of leaves, stem diameter, growing media temperature, growing media pH, leaf color, and plant survival percentage. Data were analyzed using analysis of variance (ANOVA), and the coefficient of variation was used to evaluate data homogeneity and experimental precision. The results showed that the application of cocopeat at different rates did not significantly affect any of the observed growth parameters of cocoa seedlings. Nevertheless, a positive growth trend was observed in several vegetative parameters in treatments containing cocopeat, particularly in maintaining stable moisture, temperature, and pH of the growing media. The low coefficients of variation across most parameters indicated that the data were homogeneous and the experiment had a high level of reliability. All treatments resulted in a 100% survival rate, indicating that cocopeat-based growing media are safe and suitable for cocoa seedling production. Therefore, cocopeat can be used as an alternative growing medium for cocoa nurseries, although adjustments in composition are necessary to optimize its benefits under local condition. Keywords: cocoa seedlings, cocopeat, cocoa, vegetative